Economic Valuation of Ayutthaya Historical Park, Thailand - KHAMRUANG, Areeya; NONTHAPOT, Sakkarin (Journal of Environmental Management and Tourism, 2022)
The objectives of this research were to study the general information of the tourists and the factors affecting the decision of tourists and to assess the economic valuation of the Ayutthaya Historical Park, Thailand. A questionnaire was used to collect data from 400 tourists. The general information of tourists was analyzed using the frequency and percentage. The relationship between the economic and social factors and the visiting ratio was analyzed, as well as the economic valuation assessment of the Ayutthaya Historical Park that was analyzed with the Individual Travel Cost Method (ITCM). The research results indicated that most traveled to experience the arts and culture and make merit. The tourists were impressed with the beautiful ancient remains, which were the arts of Ayutthaya and the peace of the Park. Furthermore, the most influential factors affecting the decision to visit the Ayutthaya Historical Park that had statistical significance were the travel cost and distance. The findings obtained from the economic valuation assessment of the Ayutthaya Historical Park applying the ITCM showed that the consumer surplus was 1,508.40 Baht/person/time, while the economic valuation of the Ayutthaya Historical Park was 1,999,500,930.91 Baht/year. The average visit was 2.61 times per year.